2003
DOI: 10.1016/s0741-5214(03)00550-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carotid artery stenting on the external carotid artery

Abstract: The more pronounced progression of arteriosclerotic disease at the orifice of the ipsilateral ECAs during the first year after carotid stenting might be due to local factors of the ICA stent. Its clinical significance in respect to the effect of the ECA as collateral supply to the brain might depend on the incidence of carotid stent rerecurrent stenosis, which was low in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 23 publications
1
35
0
2
Order By: Relevance
“…Mid-to long-term follow-ups were primarily focused on patency rates of ICA and restenosis rates of carotid stents. Only a few studies (12)(13)(14)(15)(16) have evaluated ECA status following carotid interventions. The present study added valuable information to our limited knowledge of ECA status following carotid interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Mid-to long-term follow-ups were primarily focused on patency rates of ICA and restenosis rates of carotid stents. Only a few studies (12)(13)(14)(15)(16) have evaluated ECA status following carotid interventions. The present study added valuable information to our limited knowledge of ECA status following carotid interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Willford-Ehringer et al reported significant progression of atherosclerotic disease at the orifice of the ipsilateral ECA after CAS compared with the contralateral ECA. 11 In one case, occlusion of the ECA due to embolism during the stenting procedure resulted in jaw claudication for up to 10 days. In our case, patient number two had prolonged symptoms of jaw claudication due to acute thrombosis of the ECA rather than embolism.…”
Section: Discussionmentioning
confidence: 98%
“…Como a taxa de RIS é baixa, a importância da CE como via colateral é reduzida. Também é descrita a ocorrência de maior progressão da lesão na CE ipsilateral ao stent, mesmo sem a sobreposição do stent na origem e oclusão da CE após o implante 162,163 .…”
Section: Efeito Do Stent Na Carotida Externaunclassified